Ni-base alloy pipes and welded joints
Patent Information
- Application Number
- JP2021083315
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-22
- Filing Date
- 2021-05-17
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-05-17
AI Technical Summary
【0014】 本発明によれば、良好な溶接部の使用性能を有する内面側ビードを安定して形成しうるNi基合金管を得ることができる。
Smart Images

Figure 0007644345000005 
Figure 0007644345000001 
Figure 0007644345000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a Ni-base alloy pipe and a welded joint. [Background technology]
[0002] In chemical plants and power plants, various plant equipment such as flue gas treatment equipment and seawater treatment equipment are installed. The inside of the plant is a severe corrosive environment where many substances that accelerate corrosion, such as chlorides and hydrogen sulfide, are present. For this reason, materials used in plant equipment are required to have not only strength but also corrosion resistance. Therefore, as disclosed in Patent Documents 1 to 8, Ni-based alloys with improved corrosion resistance have been developed for use in plant equipment. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 54-110918 [Patent Document 2] Japanese Patent Application Publication No. 63-89637 [Patent Document 3] Japanese Patent Application Publication No. 2-156034 [Patent Document 4] Japanese Patent Application Publication No. 3-173732 [Patent Document 5] Japanese Patent Application Publication No. 5-271832 [Patent Document 6] Japanese Patent Application Publication No. 9-87786 [Patent Document 7] Japanese Patent Application Publication No. 10-30140 [Patent Document 8] JP 2012-72446 A Summary of the Invention [Problem to be solved by the invention]
[0004] Some plant equipment is manufactured by assembling components together through welding. In such equipment, the state of weld bead formation can affect the progress of corrosion.
[0005] For example, some heat exchangers are manufactured by butt-welding and connecting multiple Ni-based alloy pipes that serve as flow paths for refrigerants, etc. When used as a heat exchanger, various corrosive fluids flow inside the pipe. In this case, if the height of the bead formed inside the pipe by welding, i.e., the excess weld height, is too high, the corrosive fluids will accumulate and thicken at the toe where the bead surface intersects with the surface of the base material. As a result, there is a problem that corrosion is more likely to progress at the toe.
[0006] On the other hand, if the amount of heat input during welding is reduced by trying to make the reinforcement height too low, the butt surfaces of the pipes do not melt completely, making it difficult to form a stable bead. As a result, there are problems in that welding defects occur and corrosive fluids are retained and concentrated in the welding defects, facilitating the progression of corrosion. However, Patent Documents 1 to 8 do not consider these problems at all.
[0007] Therefore, even if a pipe is manufactured using a highly corrosion-resistant Ni-based alloy, it is difficult to form a bead of an appropriate shape on the pipe during butt welding, which is less susceptible to corrosion. In other words, there is a problem in that it is difficult to obtain a Ni-based alloy pipe in which a bead is stably formed on the inner surface during welding and the weld height is not too high.
[0008] In view of the above, an object of the present invention is to provide a Ni-base alloy pipe and welded joint that can solve the above problems and stably form an inner bead having good usability at the weld. [Means for solving the problem]
[0009] The present invention has been made to solve the above problems, and the gist of the present invention is the following Ni-base alloy pipe and welded joint.
[0010] (1) Chemical composition, in mass%, C: 0.001 to 0.050%, Si: 0.05 to 0.50%, Mn: 0.05 to 1.00%, P: 0.025% or less, S: 0.0001 to 0.0030%, Fe: 18.0-40.0%, Cu: 1.50-3.00%, Co: 0.01 to 0.80%, Cr: 19.5-23.5%, Mo: 2.4-3.6%, W: 0.01 to 0.80%, Ti: 0.50-1.20%, N: 0.0010~0.0200%, Al: 0.001 to 0.200%, O: 0.0004 to 0.0120%, Sn: 0 to 0.030%, The balance is Ni and impurities. A Ni-based alloy tube that satisfies the following formula (i): 0.0010≦S+2O+0.2Sn≦0.0220 (i) In the above formula, the element symbols represent the content (mass%) of each element contained in the Ni-based alloy, and when no element is contained, the value is set to zero.
[0011] (2) The Ni-based alloy tube according to (1) above, wherein the arithmetic mean roughness Ra on the inner surface side of the Ni-based alloy tube in the longitudinal direction of the tube is 9.0 μm or less.
[0012] (3) The chemical composition contains, in mass%, replacing a part of the Ni, V: 0.40% or less, Nb: 0.40% or less, Ta: 0.40% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, B: 0.0100% or less, and REM: 0.0800% or less, The Ni-base alloy tube according to the above (1) or (2), comprising one or more selected from the following:
[0013] (4) A welded joint using the Ni-based alloy pipe according to any one of (1) to (3) above. Effect of the Invention
[0014] According to the present invention, it is possible to obtain a Ni-base alloy pipe capable of stably forming an inner bead having good usability at the welded portion. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a diagram showing a groove shape in the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present inventors have conducted research into beads of Ni-based alloy pipes and have obtained the following findings (a) to (d).
[0017] (a) The shape of the bead on the inner surface of a pipe formed during butt welding is affected by the contents of S and O contained in the Ni-base alloy pipe. The inventors have clarified that when the contents of S and O are low, the bead on the inner surface is not stably formed, and part of the butt surface remains unmelted.
[0018] On the other hand, if the S and O contents are excessive, the bead will be stably formed, but the bead will have an excessively high reinforcement height. Therefore, when used as an alloy pipe, corrosive fluid will remain near the bead, and corrosion will progress easily. Therefore, in order to stably form the bead and prevent the reinforcement height from becoming excessively high, it is necessary to adjust the S and O contents to a predetermined range.
[0019] (b) The reasons why S and O affect the formation of the bead are thought to be as follows. S and O are surface active elements, which strengthen the inward convection in the weld pool during welding. As a result, the welding heat is more easily transmitted in the depth direction, and the bead can be formed stably. On the other hand, if S and O are contained in excess, the surface tension of the molten metal decreases excessively, and the molten metal is more likely to droop. As a result, the bead shape becomes excessively raised and convex (hereinafter simply referred to as "convex shape"), and the excess weld height becomes large.
[0020] (c) In addition, the shape of the bead on the inner surface of the pipe is affected by the surface roughness in the longitudinal direction of the inner surface of the pipe. The inventors have clarified that when the surface roughness is large, the height of the weld metal increases and the weld metal tends to have a convex shape. For this reason, it is desirable to control the surface roughness within a predetermined range. In particular, when the surface roughness in the longitudinal direction of the inner surface of the pipe is large, the spread of the molten metal in the width direction is suppressed, and the shape of the bead tends to be convex and the height of the weld metal tends to be large.
[0021] (d) Furthermore, the inventors have also clarified that the shape of the inner bead is also affected by the Sn content. When Sn is contained, the penetration depth increases, and the inner bead is more likely to be formed stably. On the other hand, when excessive Sn is contained, the penetration becomes excessive, and the inner bead is more likely to have a convex shape. This is thought to be because Sn evaporates from the surface of the molten pool during welding, increasing the concentration of the arc. Therefore, when Sn is contained, in order to obtain an inner bead of an appropriate shape, it is necessary to control the Sn content within a specified range and to make the relationship between the S content, the O content, and the Sn content satisfy specified ranges.
[0022] The present invention has been made based on the above findings. Each of the features of the present invention will be described in detail below.
[0023] 1. Chemical composition of alloy tubes The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."
[0024] C: 0.001 to 0.050% If C is contained in excess, it will combine with Cr due to the welding heat cycle to form carbides at the grain boundaries in the weld heat affected zone. This will cause a Cr depleted layer near the grain boundaries, lowering corrosion resistance. For this reason, the C content is set to 0.050% or less. The C content is preferably set to 0.025% or less, more preferably set to 0.020% or less, and even more preferably set to 0.015% or less. From the viewpoint of corrosion resistance, it is desirable to reduce the C content as much as possible, but if the C content is reduced excessively, the manufacturing cost will increase. For this reason, the C content is set to 0.001% or more. The C content is preferably set to 0.002% or more, more preferably set to 0.003% or more, and even more preferably set to 0.005% or more.
[0025] Silicon: 0.05 to 0.50% Si has a deoxidizing effect. Therefore, the Si content is set to 0.05% or more. The Si content is preferably set to 0.08% or more, more preferably set to 0.10% or more, and even more preferably set to 0.12% or more. However, excessive Si content reduces the structural stability of the alloy and increases the weld crack susceptibility. In addition, it may become difficult to stably form a bead on the inner side. Therefore, the Si content is set to 0.50% or less. The Si content is preferably set to 0.48% or less, more preferably set to 0.45% or less, and even more preferably set to 0.40% or less.
[0026] Mn: 0.05 to 1.00% Mn has a deoxidizing effect similar to Si. It also has an effect of enhancing the structural stability and contributes to the stable formation of beads on the inner side. For this reason, the Mn content is set to 0.05% or more. The Mn content is preferably set to 0.10% or more, more preferably set to 0.15% or more, and even more preferably set to 0.20% or more. However, excessive Mn content reduces hot workability. For this reason, the Mn content is set to 1.00% or less. The Mn content is preferably set to 0.90% or less, and more preferably set to 0.80% or less. The Mn content is even more preferably set to 0.70% or less.
[0027] P:0.025% or less P is contained in Ni-based alloys as an impurity and significantly increases weld crack susceptibility. For this reason, the P content is set to 0.025% or less. The P content is preferably set to 0.023% or less, and more preferably set to 0.020% or less. It is preferable to reduce the P content as much as possible, but excessive reduction increases manufacturing costs. For this reason, the P content is preferably set to 0.001% or more, and more preferably set to 0.002% or more.
[0028] S: 0.0001 to 0.0030% S is generally contained in Ni-based alloys as an impurity, but in the alloy pipe of the present invention, together with O, it has the effect of enhancing the ability to form an inner bead during welding. For this reason, the S content is set to 0.0001% or more. The S content is preferably set to 0.0002% or more, and more preferably set to 0.0003% or more. However, if S is contained in excess, the bead on the inner surface of the pipe becomes convex and the weld crack susceptibility increases. For this reason, the S content is set to 0.0030% or less. The S content is preferably set to 0.0025% or less, and more preferably set to 0.0020% or less. Note that S must satisfy the formula (i) described below with respect to O and Sn.
[0029] Fe: 18.0-40.0% Fe is effective in improving hot workability. In addition, it also contributes to reducing alloy costs. For this reason, the Fe content is set to 18.0% or more. The Fe content is preferably set to 18.5% or more, and more preferably set to 19.0% or more. The Fe content is further preferably set to 25.0% or more. However, excessive Fe content reduces structural stability. For this reason, the Fe content is set to 40.0% or less. The Fe content is preferably set to 39.5% or less, and more preferably set to 39.0% or less. The Fe content is further preferably set to 35.0% or less.
[0030] Cu: 1.50-3.00% Cu has the effect of increasing the structural stability and improving the corrosion resistance in an environment where non-oxidizing acids and chlorides are present. Therefore, the Cu content is set to 1.50% or more. The Cu content is preferably set to 1.52% or more, more preferably set to 1.55% or more, and even more preferably set to 1.57% or more. However, excessive Cu content reduces hot workability. Therefore, the Cu content is set to 3.00% or less. The Cu content is preferably set to 2.98% or less, more preferably set to 2.95% or less. The Cu content is even more preferably set to 2.80% or less.
[0031] Co: 0.01 to 0.80% Like Cu, Co also has the effect of enhancing structural stability. For this reason, the Co content is set to 0.01% or more. The Co content is preferably set to 0.02% or more, and more preferably set to 0.03% or more. The Co content is further preferably set to 0.05% or more. However, since Co is a very expensive element, excessive inclusion of Co significantly increases the manufacturing cost. For this reason, the Co content is set to 0.80% or less. The Co content is preferably set to 0.78% or less, more preferably set to 0.75% or less, and further preferably set to 0.70% or less.
[0032] Cr: 19.5~23.5% Cr is an essential element for ensuring corrosion resistance. Cr forms a passive film on the surface, and improves corrosion resistance in an oxidizing acid environment. For this reason, the Cr content is set to 19.5% or more. The Cr content is preferably set to 19.7% or more, more preferably set to 20.0% or more, and even more preferably set to 20.2% or more. However, if Cr is contained in excess, the structural stability decreases. For this reason, the Cr content is set to 23.5% or less. The Cr content is preferably set to 23.0% or less, more preferably set to 22.5% or less, and even more preferably set to 22.3% or less.
[0033] Mo: 2.4-3.6% Mo improves corrosion resistance in an environment where non-oxidizing acids and chlorides are present. For this reason, the Mo content is set to 2.4% or more. The Mo content is preferably set to 2.6% or more, more preferably set to 2.8% or more, and even more preferably set to 2.9% or more. However, if Mo is contained in excess, the structural stability decreases. Furthermore, since Mo is an expensive element, the manufacturing cost increases. For this reason, the Mo content is set to 3.6% or less. The Mo content is preferably set to 3.4% or less, more preferably set to 3.2% or less, and even more preferably set to 3.1% or less.
[0034] W: 0.01 to 0.80% Like Mo, W improves corrosion resistance in an environment where non-oxidizing acids and chlorides are present. For this reason, the W content is set to 0.01% or more. The W content is preferably set to 0.02% or more, more preferably set to 0.03% or more, and even more preferably set to 0.04% or more. However, if W is contained in excess, the structural stability decreases. In addition, since W is an expensive element, the manufacturing cost increases. For this reason, the W content is set to 0.80% or less. The W content is preferably set to 0.70% or less, more preferably set to 0.60% or less, and even more preferably set to 0.50% or less.
[0035] Ti: 0.50-1.20% Ti forms carbides, contributes to strengthening, and suppresses the formation of Cr carbides, thereby reducing the deterioration of corrosion resistance at grain boundaries. Therefore, the Ti content is set to 0.50% or more. The Ti content is preferably set to 0.55% or more, more preferably set to 0.60% or more, and even more preferably set to 0.65% or more. However, if Ti is contained excessively, a large amount of Ti carbides and carbonitrides are precipitated, and ductility is reduced. Therefore, the Ti content is set to 1.20% or less. The Ti content is preferably set to 1.00% or less, more preferably set to 0.80% or less, and even more preferably set to 0.75% or less.
[0036] N: 0.0010~0.0200% N contributes to structural stability and has the effect of enhancing pitting corrosion resistance. Therefore, the N content is set to 0.0010% or more. The N content is preferably set to 0.0020% or more, more preferably set to 0.0030% or more, and even more preferably set to 0.0040% or more. However, if N is contained excessively, nitrides precipitate and the ductility decreases. Therefore, the N content is set to 0.0200% or less. The N content is preferably set to 0.0180% or less, more preferably set to 0.0150% or less, and even more preferably set to 0.0130% or less.
[0037] Al: 0.001 to 0.200% Al has a deoxidizing effect. It also contributes to oxidation resistance at high temperatures. For this reason, the Al content is set to 0.001% or more. The Al content is preferably set to 0.005% or more, and more preferably set to 0.010% or more. The Al content is preferably set to 0.020% or more. However, if Al is contained in excess, it combines with oxygen, reducing cleanliness and hot workability. Also, it may be difficult to stably form a bead on the inner side. For this reason, the Al content is set to 0.200% or less. The Al content is preferably set to 0.180% or less, and more preferably set to 0.160% or less. The Al content is further preferably set to 0.150% or less.
[0038] O: 0.0004 to 0.0120% O is generally contained as an impurity in Ni-based alloys, but in the alloy pipe of the present invention, together with S, it has the effect of enhancing the ability to form a bead on the inner surface of the pipe during welding. For this reason, the O content is set to 0.0004% or more. The O content is preferably set to 0.0006% or more, and more preferably set to 0.0008% or more. However, if O is contained in excess, the bead on the inner surface of the pipe becomes convex and the hot workability is reduced. For this reason, the O content is set to 0.0120% or less. The O content is preferably set to 0.0100% or less, and more preferably set to 0.0080% or less. Note that O, together with S and Sn, must satisfy the formula (i) described below.
[0039] In addition to the above elements, the chemical composition may further contain Sn within the range shown below.
[0040] Sn: 0 to 0.030% Sn has the effect of increasing the penetration depth during welding and enhancing the ability to form a bead on the inner side of the pipe. Therefore, it may be contained as necessary. However, if Sn is contained in excess, it reduces hot workability and increases susceptibility to weld cracking. In addition, the bead on the inner side is likely to have a convex shape. For this reason, the Sn content is set to 0.030% or less. The Sn content is preferably set to 0.028% or less, and more preferably set to 0.025% or less. On the other hand, in order to obtain the above effect, the Sn content is preferably set to 0.001% or more, more preferably set to 0.002% or more, and even more preferably set to 0.003% or more. In addition, Sn needs to satisfy the formula (i) described below with respect to S and O.
[0041] As described above, S, O, and Sn effectively contribute to the formation of beads on the inner surface of the tube, so in the Ni-base alloy tube according to the present invention, it is necessary to satisfy the following formula (i), which is a relational expression between the S content, the O content, and the Sn content.
[0042] 0.0010≦S+2O+0.2Sn≦0.0220 (i) In the above formula, the element symbols represent the content (mass%) of each element contained in the Ni-based alloy, and when no element is contained, it is set to zero. In addition, in the above formula, when the Sn content is less than 0.001%, Sn=0 is used.
[0043] S and O are surface active elements, and have the effect of strengthening the inward convection in the molten pool during welding. In addition, Sn contributes to the formation of an arc current path, and has the effect of increasing the concentration of the arc. It also transports the welding heat in the depth direction to the center of the molten pool. As a result, these elements have the effect of stably forming an inner bead, but if the value in formula (i) is less than 0.0010%, this effect cannot be obtained. For this reason, the value in formula (i) is set to 0.0010% or more. The value in formula (i) is preferably set to 0.0012% or more, and more preferably set to 0.0015% or more.
[0044] On the other hand, if the value in equation (i) exceeds 0.0220%, the surface tension of the molten metal decreases, or melting in the center of the molten pool is promoted, causing sagging. As a result, the bead becomes convex, and it becomes difficult to stably form a bead on the inner surface of the pipe. For this reason, the value in equation (i) is set to 0.0220% or less. The value in equation (i) is preferably set to 0.0215% or less, and more preferably set to 0.0210% or less.
[0045] In addition to the above elements, the chemical composition may contain one or more elements selected from V, Nb, Ta, Ca, Mg, B, and REM within the ranges shown below. The reasons for limiting each element will be explained below.
[0046] V:0.40% or less V combines with carbon to form carbides, and suppresses the generation of Cr carbides, thereby reducing the deterioration of corrosion resistance at grain boundaries. Therefore, V may be included as necessary. However, if V is included in excess, a large amount of V carbides and carbonitrides precipitate, and ductility decreases. Therefore, the V content is set to 0.40% or less. The V content is preferably set to 0.35% or less, and more preferably set to 0.30% or less. On the other hand, in order to obtain the above effect, the V content is preferably set to 0.01% or more, and more preferably set to 0.02% or more.
[0047] Nb: 0.40% or less Like V and Ti, Nb also combines with carbon to form carbides, and suppresses the formation of Cr carbides, thereby reducing the deterioration of corrosion resistance at grain boundaries. Therefore, Nb may be included as necessary. However, if Nb is included in excess, a large amount of Nb carbides and carbonitrides precipitate, reducing ductility. Furthermore, weld crack susceptibility increases. Therefore, the Nb content is set to 0.40% or less. The Nb content is preferably set to 0.35% or less, and more preferably set to 0.30% or less. On the other hand, in order to obtain the above effect, the Nb content is preferably set to 0.01% or more, and more preferably set to 0.02% or more.
[0048] Ta:0.40% or less Ta has the effect of promoting the formation of a passive film of Cr and improving corrosion resistance. Therefore, it may be contained as necessary. However, if Ta is contained in excess, a large amount of Ta carbide is precipitated, and ductility is reduced. Therefore, the Ta content is set to 0.40% or less. The Ta content is preferably set to 0.35% or less, and more preferably set to 0.30% or less. On the other hand, in order to obtain the above effect, the Ta content is preferably set to 0.01% or more, and more preferably set to 0.02% or more.
[0049] Ca:0.0100% or less Ca has the effect of improving hot workability. Therefore, it may be contained as necessary. However, if Ca is contained in excess, it combines with oxygen and significantly reduces cleanliness. As a result, hot workability is deteriorated. Therefore, the Ca content is set to 0.0100% or less. The Ca content is preferably set to 0.0080% or less, and more preferably set to 0.0060% or less. On the other hand, in order to obtain the above effect, the Ca content is preferably set to 0.0005% or more, and more preferably set to 0.0010% or more.
[0050] Mg: 0.0100% or less Like Ca, Mg has the effect of improving hot workability. Therefore, it may be contained as necessary. However, if Mg is contained in excess, it combines with oxygen and significantly reduces cleanliness. As a result, hot workability is deteriorated. Therefore, the Mg content is set to 0.0100% or less. The Mg content is preferably set to 0.0080% or less, and more preferably set to 0.0060% or less. On the other hand, in order to obtain the above effect, the Mg content is preferably set to 0.0005% or more, and more preferably set to 0.0010% or more.
[0051] B: 0.0100% or less B has the effect of segregating to grain boundaries at high temperatures, strengthening the grain boundaries, and improving hot workability. Therefore, it may be contained as necessary. However, if B is contained in excess, the weld crack susceptibility increases. Therefore, the B content is set to 0.0100% or less. The B content is preferably set to 0.0080% or less, and more preferably set to 0.0060% or less. On the other hand, in order to obtain the above effect, the B content is preferably set to 0.0002% or more, and more preferably set to 0.0005% or more.
[0052] REM: 0.0800% or less Like Ca and Mg, REM has the effect of improving hot workability during manufacturing. Therefore, it may be contained as necessary. However, if REM is contained in excess, it combines with oxygen and significantly reduces cleanliness. As a result, hot workability is rather reduced. Therefore, the REM content is set to 0.0800% or less. The REM content is preferably set to 0.0600% or less, and more preferably set to 0.0500% or less. On the other hand, in order to obtain the above effect, the REM content is preferably set to 0.0005% or more, and more preferably set to 0.0010% or more. Here, REM refers to Sc, Y, and lanthanoids, and the REM content refers to the total content of these elements.
[0053] In the chemical composition of the Ni-based alloy according to the present invention, the balance is Ni and impurities. Here, the term "impurities" refers to components that are not intentionally added but are mixed in due to various factors such as raw materials and manufacturing processes when the Ni-based alloy is industrially manufactured, and are permissible within a range that does not adversely affect the present invention.
[0054] 2. Surface roughness of alloy pipes The bead is formed when the end of the alloy pipe is welded. In order to form a good bead, it is preferable to control the arithmetic mean roughness Ra in the longitudinal direction on the inner surface side of the alloy pipe. Here, the surface roughness of the alloy pipe refers to the surface roughness after the final process in the manufacturing process. In other words, the surface roughness of the alloy pipe changes during the manufacturing process, but in order to obtain the effects of the present invention, it is sufficient that the surface roughness in the longitudinal direction of the pipe after the final process satisfies the range specified by the present invention, regardless of the surface roughness during manufacturing.
[0055] If the arithmetic mean roughness Ra of the inner surface of the Ni-based alloy pipe in the longitudinal direction of the pipe exceeds 9.0 μm, the weld metal is prevented from wetting on the inner surface of the pipe, and the weld metal is less likely to spread in the width direction, i.e., along the circumference of the pipe. As a result, the bead is likely to have a convex shape, and the weld height is likely to be large. For this reason, the arithmetic mean roughness Ra of the inner surface of the Ni-based alloy pipe in the longitudinal direction of the pipe is preferably 9.0 μm or less. The arithmetic mean roughness Ra is preferably 7.0 μm or less, and more preferably 5.0 μm or less. The lower limit of the arithmetic mean roughness Ra is not particularly set, but when the manufacturing method described later is used, it is usually 0.1 to 1.0 μm or more.
[0056] Here, the arithmetic mean roughness Ra is defined in JIS B 0601:2001, and can be measured using a contact type surface roughness measuring device.
[0057] 3. Welded joints A welded joint of Ni-base alloy pipe can be obtained by butt welding the ends of the above Ni-base alloy pipes together under specified conditions. A welded joint of Ni-base alloy pipe has a weld metal, which is a joint formed by solidifying molten metal, and a base material. The base material includes a weld heat-affected zone that is affected by heat input due to welding. The base material excluding the weld heat-affected zone inherits the chemical composition, surface roughness, and other characteristics of the Ni-base alloy pipe described in items 1 and 2 above. The weld refers to the weld metal and the weld heat-affected zone.
[0058] 4. Manufacturing method A preferred method for producing the Ni-based alloy tube according to the present invention will be described. The Ni-based alloy tube according to the present invention can obtain the effects as long as it has the above-mentioned configuration regardless of the production method, but can be stably produced, for example, by the following production method.
[0059] 4-1.Ni-based alloy tube First, a Ni-based alloy ingot is produced as a material for the Ni-based alloy pipe. The Ni-based alloy ingot is preferably produced by melting an alloy having the above-mentioned chemical composition in an electric furnace or the like, removing impurities by refining, and then casting the melt. Next, the obtained ingot is preferably hot forged into a cylindrical billet. The obtained billet is then processed to form into a pipe shape.
[0060] Specifically, it is preferable to perform cold rolling or cold drawing after hot extrusion of the billet. During processing, softening heat treatment and intermediate pickling may be performed in between, if necessary. Then, it is preferable to perform solution treatment on the alloy pipe as a heat treatment. After the solution treatment, pickling or processing may be performed, if necessary.
[0061] Here, in order to make the arithmetic mean roughness Ra of the tube in the longitudinal direction 9.0 μm or less, it is preferable to carry out the following steps. Specifically, it is preferable to carry out the solution treatment under conditions of heating in the temperature range of 950° C. to 1230° C. for 1 to 15 minutes and water cooling. It is also preferable to carry out any one of machining such as grinding and shot blasting or shot peening on the inner surface of the tube.
[0062] Although the arithmetic mean roughness Ra changes during the manufacturing process, the effect of the present invention is affected only by the surface roughness in the longitudinal direction of the pipe after the final process, regardless of the surface roughness during the intermediate processes.
[0063] 4-2. Welded joints of Ni-based alloy pipes A welded joint can be obtained by welding the end of the alloy pipe using the Ni-based alloy pipe according to the present invention as a material. The welding method is not particularly limited, but for example, arc welding may be used. In addition, the conditions for arc welding are preferably, for example, a heat input in the range of 4 to 20 kJ / cm. In addition, during welding, Ar gas is preferably used as a shielding gas and a back shielding gas. The flow rate of the gas flowing through the welding portion is preferably adjusted appropriately.
[0064] The chemical composition of the welding material (filler metal) used is not particularly limited, but is preferably as follows: In mass%, it preferably contains C: 0.150% or less, Si: 1.00% or less, Mn: 3.50% or less, P: 0.030% or less, S: 0.0001-0.0100%, Fe: 38.0% or less, Cu: 3.00% or less, Co: 15.0% or less, Cr: 14.0-26.0%, Mo: 17.0% or less, W: 4.5% or less, at least one of Nb and Ta in total 4.20% or less, Ti: 1.50% or less, V: 0.35% or less, N: 0.0500% or less, Al: 1.50% or less, O: 0.0004-0.0120%, with the balance being Ni and impurities, and the relationship between the S and O contents preferably satisfies the following formula (a).
[0065] 0.0010≦S+2O≦0.0220 (a) In the above formula, the element symbols represent the content (mass%) of each element contained in the welding material, and if no element is contained, the content is set to zero.
[0066] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES
[0067] An alloy having the chemical composition shown in Table 1 was melted and an ingot was manufactured. After that, hot forging and hot rolling were performed to adjust the thickness to 10 mm. Next, the scale formed on the surface was removed by pickling. At this time, the arithmetic mean roughness Ra was about 12 μm for all steel types. After that, assuming the manufacturing process of alloy pipes, a 3 mm alloy plate was obtained by cold rolling while performing softening heat treatment and intermediate pickling on the way.
[0068] Next, the alloy plate was subjected to solution treatment in a hydrogen furnace at 1150°C for 10 minutes and then water-cooled. After that, plate materials with a width of 50 mm and a length of 100 mm were cut out from the alloy plate. Then, for some of the cut-out plate materials, shot peening was performed on only one side, assuming the inner surface side of the alloy pipe, as shown in Table 2. For the plate materials that were not shot peened, one side was ground or polished 1 to 5 times using a grindstone with a grit size of 40 or 60. In Table 2, for example, polishing (#40 x 1 time) indicates that polishing was performed once with a grindstone with a grit size of 40.
[0069] [Table 1]
[0070] [Table 2]
[0071] The arithmetic mean roughness of each plate material was measured using a contact roughness meter. Two plates of each alloy type were prepared, and the end faces in the rolling direction were grooved as shown in Figure 1. The grooved end faces of these plates were butted together, and a filler metal with an outer diameter of 1.0 mm and the chemical composition shown in Table 3 was used to perform first layer welding to obtain a welded joint. The heat input during welding was approximately 5 kJ / cm, and Ar gas was used for the shielding gas and back shielding gas, and it was flowed at a flow rate of 10 L / min in the welding area.
[0072] [Table 3]
[0073] For the welded joints obtained, those in which a back bead was formed along the entire length of the weld line were judged to have no problem with the ability to form a bead on the inner surface of the alloy pipe, and were rated as "passed." Among them, those in which the width of the back bead was 2 mm or more along the entire length of the weld line were rated as "excellent," and those in which a back bead of 1 mm or more was formed, but with a width below 2 mm, were rated as "fair." In this example, the back bead corresponds to the inner bead formed when welding is performed from the outside of the alloy pipe.
[0074] After that, three cross sections were taken from the welded joint, and in all cross sections, those in which the back bead height was 1.0 mm or less were judged to have a good shape of the inner bead of the alloy pipe, and were rated as "passed." Among them, those in which the back bead height was 0.8 mm or less in all cross sections were rated as "excellent," and the rest were rated as "fair." The results are summarized in Table 4 below.
[0075] [Table 4]
[0076] All of the test specimens using alloys A to H and L to N satisfied the requirements of the present invention, and the formability and shape of the bead on the back side were good. Among these, test specimen N1 using alloy N satisfied the range of the requirements of formula (i), and therefore satisfied both the formability and height of the bead on the back side.
[0077] On the other hand, the S and O contents of specimens I1 and K1, which used alloys I and K, did not satisfy formula (i) and were higher than the specified range. As a result, the molten metal sagged significantly and the height of the bead on the back side did not meet the target. The relationship between the S and O contents of specimen J1, which used alloy J, did not satisfy formula (i) and was lower than the specified range. As a result, melting in the plate thickness direction was insufficient, and the target ability to form a bead on the back side was not achieved.
[0078] Similarly, the test piece O1, which used alloy type O, had a lower content of S, O, and Sn than the range specified by formula (i). As a result, melting in the thickness direction was insufficient, and the formation ability of the bead on the back side did not meet the target. In addition, the test pieces P1 and Q1, which used alloy types P and Q1, had higher S, O, and Sn contents than the range specified by formula (i), or the Sn content exceeded the specified range. As a result, the molten metal sagged significantly, and the target bead height on the back side was not met. [Industrial Applicability]
[0079] According to the present invention, it is possible to obtain a Ni-base alloy pipe in which an inner bead is stably formed during butt welding and the bead height is not excessive.
Claims
1. The chemical composition, in mass%, is C: 0.001-0.050%, Si: 0.05-0.50%, Mn: 0.05-1.00%, P: 0.025% or less, S: 0.0001-0.0030%, Fe: 18.0-40.0%, Cu: 1.50-3.00%, Co: 0.01 to 0.80%, Cr: 19.5-23.5%, Mo: 2.4-3.6%, W: 0.01-0.80%, Ti: 0.50-1.20%, N: 0.0010-0.0200%, Al: 0.001-0.200%, O: 0.0004-0.0120%, Sn: 0 to 0.030%, The balance is Ni and impurities. A Ni-based alloy tube that satisfies the following formula (i): 0.0010≦S+2O+0.2Sn≦0.0220...(i) In the above formula, the element symbols represent the content (mass%) of each element contained in the Ni-based alloy, and when no element is contained, the value is set to zero.
2. 2. The Ni-based alloy pipe according to claim 1, wherein an arithmetic mean roughness Ra of the inner surface of the Ni-based alloy pipe in the longitudinal direction of the pipe is 9.0 μm or less.
3. The chemical composition is, in mass%, replacing a part of the Ni, V: 0.40% or less, Nb: 0.40% or less, Ta: 0.40% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, B: 0.0100% or less, and REM: 0.0800% or less, The Ni-base alloy tube according to claim 1 or 2, comprising one or more selected from the following:
4. A welded joint using the Ni-based alloy pipe according to any one of claims 1 to 3.
Citation Information
Patent Citations
Manufacturing method of alloy tubular product
CN102527724A
Alkali-corrosion-resistant nickel-based alloy
CN108441703A
Anticorrosion nickel alloy
JP1979110918A
Corrosion resistant high strength nickel base alloy
JP1988089637A
Alloy based on anticorrosive nickel
JP1990156034A